Smart Teaching: The Synergy of Multiple Intelligences and Artificial Intelligence in English as a Foreign Language Instruction - M. Pitychoutis, Konstantinos; Al Rawahi, Ahmed (Forum for Linguistic Studies, 2024)
This article investigates the integration of Howard Gardner’s Multiple Intelligences (MI) theory with Artificial Intelligence (AI) tools in English as a Foreign Language (EFL) instruction. MI theory, which highlights diverse cognitive strengths, has been transformative in inclusive education, while AI tools, such as chatbots, offer personalised feedback, interactive learning environments, and differentiated instruction that align with MI principles. By adopting a conceptual research design, this study synthesises existing literature and case studies to propose strategies for engaging various intelligences using AI technologies. Key applications include personalised feedback for linguistic and logical-mathematical learners, immersive simulations for spatial intelligence, and collaborative platforms to support interpersonal intelligence. Practical strategies for integrating AI tools into MI-based instruction are discussed, alongside considerations for tailoring educational experiences to diverse learner profiles. Ethical concerns, such as data privacy and algorithmic bias, are addressed, emphasising the importance of responsible AI integration and teacher training to maximise these tools’ potential. The study provides a robust pedagogical framework showcasing the synergy between MI theory and AI technologies, demonstrating how this approach can enhance engagement, motivation, and inclusivity in EFL classrooms. While conceptual, the study lays the groundwork for future empirical research and underscores the potential of AI-enhanced MI-based instruction in fostering dynamic and equitable language learning environments.